Outcomes of Short Fusion versus Long Fusion for Adult Degenerative Scoliosis: A Systematic Review and Meta‐analysis. Issue 4 (27th November 2017) - Phan, Kevin; Xu, Joshua; Maharaj, Monish M; Li, Julian; Kim, Jun S; Di Capua, John; Somani, Sulaiman; Tan, Kimberly‐Anne; Mobbs, Ralph J; Cho, Samuel K
Abstract : The objective of this study was to evaluate differences in clinical and radiographic outcomes between short (<3 levels) and long (≥3 levels) fusions in the setting of degenerative lumbar scoliosis. A literature search was performed from six electronic databases. The key terms of "degenerative scoliosis" OR "lumbar scoliosis" AND "fusion" were combined and used as MeSH subheadings. From relevant studies identified, demographic data, complication rates, Oswestry Disability Index (ODI), and radiographic parameters were extracted and the data was pooled and analyzed. Long fusion was associated with comparable overall complication rates to short fusion (17% vs 14%, P = 0.20). There was a significant difference in the incidence of pulmonary complications when comparing short versus long fusion (0.42% vs 2.70%; P = 0.02). No significant difference was found in terms of motor, sensory complications, infections, construct‐related or cardiac complications, pseudoarthrosis, dural tears, cerebrospinal fluid (CSF) leak, or urinary retention. A longer fusion was associated with a greater reduction in coronal Cobb angle and increases in lumbar lordosis, but both findings failed to achieve statistical significance. The ODI was comparable across both cohorts. If shorter fusion lengths are clinically indicated, they should be used instead of longer fusion lengths to reduce perioperative time, costs, and some other complications. However, there are no statistically significant differences in terms of radiographically measurable restoration associated with a short or long fusion.